A look at typological influences in the development of switch-reference systems in Highlands Papua New Guinea and Australia - Banks, Jonathan (Journal of Language and Culture, 2023)
In this paper I describe the main characteristics of switch-reference systems of two regions, Highlands Papua New Guinea and Australia and show how certain underlying, general typological characteristics of languages of these regions inform and shape the nature of their switch-reference morpho-syntax and its paths of development through time. A core aspect of the differing characteristics of switch-reference systems of New Guinea and Australia is the predominating type of clause combining structure of each region, clause chaining in New Guinea vs clause embedding in Australia. I claim that this basic distinction is the basis through which the differing manifestations of switch-reference systems in each region develop diachronically.